Patterns of domestic exposure to carbon monoxide and particulate matter in households using biomass fuel in Janakpur, Nepal. (January 2017) - Bartington, S.E.; Bakolis, I.; Devakumar, D.; Kurmi, O.P.; Gulliver, J.; Chaube, G.; Manandhar, D.S.; Saville, N.M.; Costello, A.; Osrin, D.; Hansell, A.L.; Ayres, J.G.
Abstract: Household Air Pollution (HAP) from biomass cooking fuels is a major cause of morbidity and mortality in low-income settings worldwide. In Nepal the use of open stoves with solid biomass fuels is the primary method of domestic cooking. To assess patterns of domestic air pollution we performed continuous measurement of carbon monoxide (CO) and particulate Matter (PM2.5 ) in 12 biomass fuel households in Janakpur, Nepal. We measured kitchen PM2.5 and CO concentrations at one-minute intervals for an approximately 48-h period using the TSI DustTrak II 8530/SidePak AM510 (TSI Inc, St. Paul MN, USA) or EL-USB-CO data logger (Lascar Electronics, Erie PA, USA) respectively. We also obtained information regarding fuel, stove and kitchen characteristics and cooking activity patterns. Household cooking was performed in two daily sessions (median total duration 4 h) with diurnal variability in pollutant concentrations reflecting morning and evening cooking sessions and peak concentrations associated with fire-lighting. We observed a strong linear relationship between PM2.5 measurements obtained by co-located photometric and gravimetric monitoring devices, providing local calibration factors of 4.9 (DustTrak) and 2.7 (SidePak). Overall 48-h average CO and PM2.5 concentrations were 5.4 (SD 4.3) ppm (12 households) and 417.6 (SD 686.4) μg/m 3 (8 households), respectively, with higher average concentrations associated with cooking and heating activities. Overall average PM2.5 concentrations and peak 1-h CO concentrations exceeded WHO Indoor Air Quality Guidelines. Average hourly PM2.5 and CO concentrations were moderately correlated (r = 0.52), suggesting that CO has limited utility as a proxy measure for PM2.5 exposure assessment in this setting. Domestic indoor air quality levels associated with biomass fuel combustion in this region exceed WHO Indoor Air Quality standards and are in the hazardous range for human health. Highlights: Intensive PM2.5 and CO monitoring was performed in 12 biomass fuel-using households in Janakpur. Domestic cooking activity patterns and kitchen, stove and fuel characteristics were recorded. Temporal PM2.5 and CO patterns demonstrated diurnal variability reflecting morning and evening cooking sessions. Average PM2.5 and peak CO concentrations both exceeded World Health Organization (WHO) Indoor Air Quality Guidelines. Concentrations of PM2.5 and CO were moderately correlated during cooking periods.